Mentalna mapa Rosji w polskiej przestrzeni językowej - Piotrowski, Łukasz (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The author of the paper tries to analyse toponyms associated with Russia which are present for himself in the Polish linguistic space. The analysis will be made from a point of view of cultural linguistics. Place-names traditionally strengthened in both languages, of which showing geographical objects was an initial function, as  a result of historical contacts between Russia and Poland obtained a new additional meaning. Presenting the meaning is the purpose of the paper, in particular with the emphasis on the way the events associated with individual Russian toponyms was reflected in Polish are interpreted. The manner of making them Polish texts in which place names associated with Russia appear will be analysed. On the basis of the context of using them and stylistic marking applying these words will be described. Moreover, the place-names will stay in the form of questionnaire presented to native users of the Polish language in order to examine the associations connected with the given place.  On the basis of the research the author made an attempt to reconstruct the mental map of Russia in the Polish linguistic space.